Cellular Prion Protein Mediates α‐Synuclein Uptake, Localization, and Toxicity In Vitro and In Vivo. Issue 1 (27th August 2021) - Thom, Tobias; Schmitz, Matthias; Fischer, Anna‐Lisa; Correia, Angela; Correia, Susana; Llorens, Franc; Pique, Anna‐Villar; Möbius, Wiebke; Domingues, Renato; Zafar, Saima; Stoops, Erik; Silva, Christopher J.; et al.
Abstract: Background: The cellular prion protein (PrP C ) is a membrane‐bound, multifunctional protein mainly expressed in neuronal tissues. Recent studies indicate that the native trafficking of PrP C can be misused to internalize misfolded amyloid beta and α‐synuclein (aSyn) oligomers. Objectives: We define PrP C 's role in internalizing misfolded aSyn in α‐synucleinopathies and identify further involved proteins. Methods: We performed comprehensive behavioral studies on four transgenic mouse models (ThySyn and ThySynPrP00, TgM83 and TgMPrP00) at different ages. We developed PrP C ‐(over)‐expressing cell models (cell line and primary cortical neurons), used confocal laser microscopy to perform colocalization studies, applied mass spectrometry to identify interactomes, and determined disassociation constants using surface plasmon resonance (SPR) spectroscopy. Results: Behavioral deficits (memory, anxiety, locomotion, etc.), reduced lifespans, and higher oligomeric aSyn levels were observed in PrP C ‐expressing mice (ThySyn and TgM83), but not in homologous Prnp ablated mice (ThySynPrP00 and TgMPrP00). PrP C colocalized with and facilitated aSyn (oligomeric and monomeric) internalization in our cell‐based models. Glimepiride treatment of PrP C ‐overexpressing cells reduced aSyn internalization in a dose‐dependent manner. SPR analysis showed that the binding affinity of PrP C to monomeric aSyn was lower than to oligomeric aSyn. Mass spectrometry‐based proteomic studies identified clathrin in the immunoprecipitates of PrP C and aSyn. SPR was used to show that clathrin binds to recombinant PrP, but not aSyn. Experimental disruption of clathrin‐coated vesicles significantly decreased aSyn internalization. Conclusion: PrP C 's native trafficking can be misused to internalize misfolded aSyn through a clathrin‐based mechanism, which may facilitate the spreading of pathological aSyn. Disruption of aSyn‐PrP C binding is, therefore, an appealing therapeutic target in α‐synucleinopathies. © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society